A TrxR inhibiting gold(I) NHC complex induces apoptosis through ASK1-p38-MAPK signaling in pancreatic cancer cells - Cheng, Xinlai; Holenya, Pavlo; Can, Suzan; Alborzinia, Hamed; Rubbiani, Riccardo; Ott, Ingo; Wölfl, Stefan (Molecular cancer, 2014)
Cancer cells in the advanced stage show aberrant antioxidant capacity to detoxify excessive ROS resulting in the compensation for intrinsic oxidative stress and therapeutic resistance. PDAC is one of the most lethal cancers and often associated with a high accumulation of ROS. Recent studies identified gold(I) NHC complexes as potent TrxR inhibitors suppressing cell growth in a wide spectrum of human malignant cell lines at the low micromolar concentration. However, the mechanism of action is not completely elucidated yet.